2022
DOI: 10.1039/d1dt04224f
|View full text |Cite
|
Sign up to set email alerts
|

Spherical V-doped nickel–iron LDH decorated on Ni3S2 as a high-efficiency electrocatalyst for the oxygen evolution reaction

Abstract: Due to the slow reaction kinetics of oxygen evolution (OER), the electrolysis rate of water is greatly limited. Therefore, it is of great significance to study stable and efficient non-noble...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…3a indicate that the sample MoS 2 /Fe-Ni 3 S 2 /NF has excellent OER performance with only a very small overpotential of 148 mV to achieve a current density of 10 mA cm −2 , which is much lower than those of NF, Ni(OH) 2 /NF, and MoS 2 /Ni 3 S 2 /NF (485 mV, 389 mV, and 229 mV, respectively) and exceeds most of the non-precious metal catalysts reported in recent years for OER in alkaline electrolytes. 47–49 The Tafel slope of the same interval obtained by LSV shows the fast reaction kinetics of the reaction catalyst in the catalytic OER. As shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…3a indicate that the sample MoS 2 /Fe-Ni 3 S 2 /NF has excellent OER performance with only a very small overpotential of 148 mV to achieve a current density of 10 mA cm −2 , which is much lower than those of NF, Ni(OH) 2 /NF, and MoS 2 /Ni 3 S 2 /NF (485 mV, 389 mV, and 229 mV, respectively) and exceeds most of the non-precious metal catalysts reported in recent years for OER in alkaline electrolytes. 47–49 The Tafel slope of the same interval obtained by LSV shows the fast reaction kinetics of the reaction catalyst in the catalytic OER. As shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Various divalent, trivalent, or high valent cations can be selected to construct nanosheets with the insertion of the multiple anions into the interlayer, forming a highly controllable flexible structure of LDHs. 14,15 Deng's group prepared CoFe-LDH nanowire arrays on graphite felt, which required overpotentials of 252 mV and 285 mV at current densities of 10 mA cm −2 and 100 mA cm −2 , respectively; 16 Yu reported that Cu@CoFe-LDH core-shell nanostructure catalyst exhibited an OER overpotential of 240 mV when the current density was 10 mA cm −2 ; 17 Li et al adopted the metal-organic framework as template to obtain NiCo-LDH/ NiCoS hybrid arrays, which delivered an OER overpotential of 308 mV at a high current density of 100 mA cm −2 in 1 M KOH solution. 18 An unfavorable problem is that the exposed active sites of bulk materials are limited by their large size and thickness, which reduces the conductivity and slows down the hydrolysis process to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, transition metal oxides, 9,10 phosphates, 11,12 sulfides, 13,14 nitrides 15,16 and layered hydroxides (LDHs) [17][18][19] have been extensively developed as transition metal based catalysts. Among them, sulfides are considered as viable electrocatalysts because of their advantages of low cost, high electrical conductivity and convenient synthesis.…”
Section: Introductionmentioning
confidence: 99%